Hereditary breast/ovarian and colorectal cancer genetics knowledge in a national sample of US physicians. Issue 10 (22nd March 2005) - Wideroff, L; Vadaparampil, S T; Greene, M H; Taplin, S; Olson, L; Freedman, A N
Abstract : Background: Clinically relevant genetics knowledge is essential for appropriate assessment and management of inherited cancer risk, and for effective communication with patients. This national physician survey assessed knowledge regarding basic cancer genetics concepts early in the process of introduction of predictive genetic testing for breast/ovarian and hereditary non-polyposis colorectal cancer (HNPCC) syndromes. Methods: A stratified random sample was selected from the American Medical Association Masterfile of all licensed physicians. In total, 1251 physicians (820 in primary care, 431 in selected subspecialties) responded to a 15 minute questionnaire (response rate 71%) in 1999–2000. Multivariate logistic regression analyses were conducted to identify demographic and practice characteristics associated with accurate response to three knowledge questions. Results: Of the study population, 37.5% was aware of paternal inheritance of BRCA1/2 mutations, and 33.8% recognised that these mutations occur in <10% of breast cancer patients. Only 13.1% accurately identified HNPCC gene penetrance as ⩾50%. Obstetrics/gynaecology physicians, oncologists, and general surgeons were significantly more likely than general and family practitioners to respond accurately to the breast/ovarian questions, as were gastroenterologists to the HNPCC question. Conclusions: These nationally representative data indicate limited physician knowledge about key cancer genetics concepts in 1999–2000, particularly among general primary care physicians. Specialists were more knowledgeable about syndromes they might treat or refer elsewhere. Recent dissemination of practice guidelines and continued expansion of relevant clinical literature may enhance knowledge over time. In addition to educational efforts to assist physicians with the growing knowledge base, more research is needed to characterise the organisational changes required within the healthcare system to provide effective cancer genetics services.